Nanoparticle-mediated codelivery of myelin antigen and a tolerogenic small molecule suppresses experimental autoimmune encephalomyelitis - Yeste, Ada; Nadeau, Meghan; Burns, Evan J; Weiner, Howard L; Quintana, Francisco J (Proceedings of the National Academy of Sciences - PNAS, 2012)
The immune response is normally controlled by regulatory T cells (Tregs). However, Treg deficits are found in autoimmune diseases, and therefore the induction of functional Tregs is considered a potential therapeutic approach for autoimmune disorders. The activation of the ligand-activated transcription factor aryl hydrocarbon receptor by 2-(1'H-indole-3'-carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE) or other ligands induces dendritic cells (DCs) that promote FoxP3(+) Treg differentiation. Here we report the use of nanoparticles (NPs) to coadminister ITE and a T-cell epitope from myelin oligodendrocyte glycoprotein (MOG)(35)(-55) to promote the generation of Tregs by DCs. NP-treated DCs displayed a tolerogenic phenotype and promoted the differentiation of Tregs in vitro. Moreover, NPs carrying ITE and MOG(35-55) expanded the FoxP3(+) Treg compartment and suppressed the development of experimental autoimmune encephalomyelitis, an experimental model of multiple sclerosis. Thus, NPs are potential new tools to induce functional Tregs in autoimmune disorders.